CRISPR Genome Editing Applied to the Pathogenic Retrovirus HTLV-1 - Panfil, Amanda R.; Green, Patrick L.; Yoder, Kristine E. (Frontiers in Cellular and Infection Microbiology, 2020)
CRISPR editing of retroviral proviruses has been limited to HIV-1. We propose human T-cell leukemia virus type 1 (HTLV-1) as an excellent model to advance CRISPR/Cas9 genome editing technologies against actively expressing and latent retroviral proviruses. HTLV-1 is a tumorigenic human retrovirus responsible for the development of both leukemia/lymphoma (ATL) and a neurological disease (HAM/TSP). The virus immortalizes and persists in CD4+ T lymphocytes that survive for the lifetime of the host. The most important drivers of HTLV-1-mediated transformation and proliferation are the tax and hbz viral genes. Tax, transcribed from the plus-sense or genome strand, is essential for de novo infection and cellular immortalization. Hbz, transcribed from the minus-strand, supports proliferation and survival of infected cells in both its protein and mRNA forms. Abrogating the function or expression of tax and/or hbz by genome editing and mutagenic double-strand break repair may disable HTLV-1-infected cell growth/survival and prevent immune modulatory effects and ultimately HTLV-1-associated disease. In addition, the HTLV-1 viral genome is highly conserved with remarkable sequence homogeneity, both within the same host and even among different HTLV isolates. This offers more focused guide RNA targeting. In addition, there are several well-established animal models for studying HTLV-1 infection in vivo as well as cell immortalization in vitro. Therefore, studies with HTLV-1 may provide a better basis to assess and advance in vivo genome editing against retroviral infections.